Nutritional supplementation, combined with a balanced diet and environmental health education, improved the conversion of LTBI and daily nutrient intake - Samsidi Suparman; Fahri Sukmal; Nur Fauziyah Roro; Dewi Maryati; Khairat Fakhrida; Sunanda Putra Egy; Juliastuti Aditya (BIO Web of Conferences)
Latent tuberculosis infection showed an iceberg phenomenon and it is also an early form of tuberculosis. This disease remains prevalent in many countries and has become a public health problem. Integration- based approaches in the form of nutritional supplement intervention combined with a balanced diet and environmental health education, may be effective in addressing latent tuberculosis. This study evaluates the efficacy of an integrated intervention model in improving specific immune responses and nutrient intake among subjects. This study employed field experimental design and random allocation techniques. This study was conducted in two HCs (Health Centers) in Bandung and Jambi, Indonesia. A total of 36 samples were taken from Garuda HC in Bandung and 36 samples from Paal Merah II HC in Jambi. Each group consisted of 36 treatment and 36 control group samples. The intervention lasted for 30 days. The control group received a balanced diet and environmental health education and the treatment group received both education-based intervention and nutritional supplementation. The results showed that the proportion of the treatment group with reduced latent tuberculosis status was higher than that of the control group (p>0.05). The treatment group also had an increase in daily nutrient intake compared to the control group (p<0.05).